Sharing Singapore’s Experience in the Management of Obstetrics COVID-19 Patients - Lim, Eda Qiao Yan; Koh, Thong Chuan Eugene; Tan, Lay Kok; Chua, Si Jack Chong Swee Boon Raymond (Archives of Clinical and Biomedical Research, 2023)
There are current guidelines for managing obstetric COVID-19 patients, however, guidelines for the initial triaging and assessing obstetric COVID-19 patients to right-site care and disposition whilst ensuring patient safety are absent. Here, Singapore’s utilization of a risk-stratified approach to manage obstetric COVID-19 patients’ recovery in a safe manner is described, and this approach also helps to preserve tertiary healthcare resources for the acutely sick. The care protocol was also progressively relaxed as more information was obtained from statistical analysis of pregnant patients’ hospitalisation and disease severity data. The information showed that disease severity in pregnant patients were generally mild, and majority of patients could recover safely at home.